ACCOUNTABILITY OF THE MARRIAGE MANAGEMENT INFORMATION SYSTEM (SIMKAH) IN THE IMPLEMENTATION OF THE MARRIAGE LAW AT THE OFFICE OF RELIGIOUS AFFAIRS - Fansori, Rosihan; Anita Handayani; Suratman; Ulum, Bahrul (JAS : Jurnal Ahwal Syakhshiyyah, 2024)
This study evaluates the accountability of the Marriage Management Information System (SIMKAH) in the implementation of the Marriage Law at the Office of Religious Affairs (KUA). Using a qualitative approach with a case study design, this study assesses the role of SIMKAH in improving the efficiency, accuracy, and transparency of marriage administration. Data was collected through in-depth interviews, observations, and document analysis. The analysis was carried out thematically, through four main stages: data reduction, coding, thematic grouping, and thematic descriptions to identify patterns related to SIMKAH accountability. The results of the study show that SIMKAH strengthens KUA's accountability by accelerating the recording process, reducing errors, and increasing access to information for related parties. However, some obstacles such as limited technology infrastructure and lack of user understanding are still challenges. This study recommends increasing training for staff and strengthening technology infrastructure to optimize the implementation of SIMKAH. These findings provide important insights for the government in developing a more accountable and transparent marriage administration system in Indonesia.